Retirement Years: How Much Money Will I Need? - Josephine Turner; Nayda Torres (EDIS, 2007)
Revised! FCS7151, an 11-page fact sheet by Josephine Turner and Nayda Torres, helps users understand how much money they will need to save for retirement. It lists possible sources of retirement income and includes hands-on worksheets that will help users calculate their specific savings needs and goals. Revised to update content. Published by the UF Department of Family, Youth and Community Sciences, September 2007.